Assessment of leadership skills among first year medical students using the authentic leadership questionnaire - Nanayakkara, U.; Dissanayaka, D.W.N. (My University, 2012)
With increased public interest to see doctors take on more significant leadership roles, it is essential to develop strong personal qualities and professional values through the medical curriculum, enabling them to become future leaders not only in the health sector but also in society in general.